AWARENESS OF THE HIRE PURCHASE LAW: A CASE STUDY IN UITM CAWANGAN TERENGGANU - Syafini Muda @ Yusof,; Nazuha Muda @ Yusof,; Zokree Abdul Karim,; Noorimah Misnan, (Journal of Islamic, Social, Economics and Development, 2024)
Hire purchase is a system of buying goods on credit. It is an agreement in which the owner leases goods to the hirer with an option to purchase and the hirer then pay the agreed amount by instalment. Throughout the instalment period, the hirer is not entitled to ownership. The Hire Purchase Act of 1967 was enacted in Malaysia in order to control the structure and substance of hire purchase agreements, the rights and obligations associated with such agreements, as well as other hire purchase-related issues. This study aims to investigate the awareness of the hire purchase law among staff at UiTM Cawangan Terengganu. A total of 247 staff were involved in this study which selected using stratified random sampling. Descriptive analyses were used to overview the demographic profiles and to determine the awareness level of the hirers regarding the Hire Purchase Law among respondents. The results of the study showed that majority of the respondents are slightly aware of their rights in Hire Purchase Agreement. Based on this finding, it is recommended for the hirer to improve knowledge and understanding related to Hire Purchase Act 1967. This is to ensure that the rights are protected.